The Relationship of Parenting Patterns with The Incident of Temper Tantrum in Preschool Age Children - Adisti, Ismi; Syafrini, Retty Octi; Nasution, Riska Amalya (Jurnal Keperawatan Universitas Jambi, 2022)
Background: Temper tantrum is an extreme emotional outburst with crying, shouting, hitting and other maladaptive activities. Temper tantrums if allowed to continue will experience disturbances in their emotional development. One of the factors that can influence is parenting. Objective: To find out the relationship between parenting patterns and the incidence of temper tantrums. Methods: This research is a quantitative descriptive study on 78 respondents using the Consecutive Sampling method with a cross-sectional approach. Primary data comes from the results of the questionnaire, the data analysis used is univariate and bivariate with a tau kendal test with a p-value of 0.05. Results: There is a relationship between parenting and the incidence of temper tantrums (p-value 0.024 r 0.179) which is low and positive, there is no relationship between authoritarian parenting (p-value 0.654 r 0.038), there is no relationship between permissive parenting (p- value = 0.313 r 0.087), there is no democratic relationship (p-value 0.313 r 0.123) and there is no relationship with indifferent parenting (p-value 0.191 r 0.119). Conclusion: Based on statistical analysis, it was found that there is a relationship between parenting patterns and the incidence of temper tantrums, therefore it is necessary to hold educational counseling about good parenting.